MANAGING ‘BALIGH’ IN FOUR MUSLIM COUNTRIES: Egypt, Tunisia, Pakistan, and Indonesia on the Minimum Age for Marriage - Ahmad Ropei; Miftachul Huda; Adudin Alijaya; Fakhry Fadhil; Fitria Zulfa (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
In Islamic law, the concept of baligh has long been debated among clerics. The debate also appears to have resulted in different rules regarding the minimum age of marriage among Muslim countries. This paper aims to reveal the maturity standard regarding the minimum age of marriage in four Muslim countries: Egypt, Pakistan, Tunisia, and Indonesia. This paper is based on library research and employs a comparative study approach. This paper argues that Egypt, Pakistan, Tunisia, and Indonesia have a different minimum age for marriage. In Egypt and Pakistan, the minimum age for marriage is 18 years for men and 16 years for women. However, Pakistan has gone further by instituting legal sanctions if the regulation of the minimum age is violated. In Tunisia, the minimum age for marriage is 18 years for men and women, while in Indonesia it is 19 years for men and women. The determination of the minimum age for marriage is intended for several purposes, including limiting the number of early marriages, reducing the divorce rate, and preparing a strong national generation through the maturity of the marriage age. These interests, from the perspective of Islamic law, are the manifestation of the principle of maslahah (fundamentally aimed at achieving goodness and rejecting harm concerning marital life).